2018
DOI: 10.1111/ecog.03698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contemporary environment and Quaternary climate change on drylands plant diversity differ between growth forms

Abstract: Previous studies on large‐scale patterns in plant richness and underlying mechanisms have mostly focused on forests and mountains, while drylands covering most of the world's grasslands and deserts are more poorly investigated for lack of data. Here, we aim to 1) evaluate the plant richness patterns in Inner Asian drylands; 2) compare the relative importance of contemporary environment, historical climate, vegetation changes, and mid‐domain effect (MDE); and 3) explore whether the dominant drivers of species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…Therefore, HHM can play a role in refugium when climate change events happened. Previous studies found that habitat heterogeneity is also the primary determinant of spatial variation of plant species richness in drylands (Liu et al, 2019), Tibetan Plateau (Mao et al, 2013), and European mountains (Svenning and Skov, 2004;Svenning et al, 2006). These results are probably caused by the refugia effects, subsequent speciation events, and limited dispersals for species in the mountains.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, HHM can play a role in refugium when climate change events happened. Previous studies found that habitat heterogeneity is also the primary determinant of spatial variation of plant species richness in drylands (Liu et al, 2019), Tibetan Plateau (Mao et al, 2013), and European mountains (Svenning and Skov, 2004;Svenning et al, 2006). These results are probably caused by the refugia effects, subsequent speciation events, and limited dispersals for species in the mountains.…”
Section: Introductionmentioning
confidence: 95%
“…Plant diversity displays distinct large-scale geographic patterns, which in turn are determined by late Quaternary and contemporary climatic conditions, both together and independently (e.g., Svenning, 2003;Kreft and Jetz, 2007;Sommer et al, 2010;Sandel et al, 2011;Wang et al, 2012a;Liu et al, 2018). A core hypothesis of biodiversity is that contemporary climates determine current plant diversity (O'brien et al, 2000;Ackerly et al, 2010;Kimball et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the influential factors considered, current climate, paleo-climate, and habitat heterogeneity are the most frequently cited explanations for the biodiversity patterns observed (Liu et al, 2018). Whether diversity patterns are caused by the current climate or by historical factors has been discussed for a long time.…”
Section: Introductionmentioning
confidence: 99%